(untitled) (Journal of Hama University, 2026)
This study aimed to identify the attitudes of secondary school principals in the city of Latakia towards the implementation of school-based management (SBM) in their schools. It also sought to explore the differences in these attitudes based on the variables of educational qualification and years of administrative experience. The study sample consisted of (32) male and female principals. The researcher employed the descriptive analytical method, and in order to achieve the study objectives, a questionnaire consisting of (37) items was developed, distributed across six domains: administrative affairs, curricula and teaching methods, personnel affairs, student affairs, school facilities, and financial affairs. The validity and reliability of the instrument were verified. Data were analyzed using the Statistical Package for the Social Sciences (SPSS).The study yielded several findings, the most significant of which were: The attitudes of secondary school principals in the city of Latakia towards the implementation of school-based management were generally high across all domains of the study, except for the domain of curricula and teaching methods. There were no statistically significant differences in principals’ responses attributed to the variable of educational qualification; however, statistically significant differences were found based on the number of years of administrative experience. The study concluded with several recommendations, the most important of which are: granting school principals greater authority, particularly in the area of delegation of powers, and organizing training programs for school administrators to support the transition to school-based management.